Pembuatan Sistem Otomasi Dispenser Menggunakan Mikrokontroler Arduino Mega 2560 - Imran Oktariawan; . Martinus; . Sugiyanto (Jurnal Ilmiah Teknik Mesin, 2013)
Developments in science and technology in this era is an important factor and can not be separated in an attempt to improve the welfare of the community. This is proved by its increasement of peoples demand for tools that can work automatically, efficiently and saving energy. One of automation technologies that can be applied in home appliances is a dispenser that uses automation.Dispenser which used in this study using a microcontroller Ardunio Mega 2560, because the microcontroller can reduce the complexity of electronic circuits and instrumentation. The microcontroller pin is used as an input and 10 PIN 2 PIN as output. Meanwhile, in the manufacturing process of hardware includes five series are: power supply circuit, sensor circuit height glass, circuit microcontroller arduino mega 2560, Soil moisture sensor connection, relay driver circuit. While data that obtained are the water level, the presence sensor cups, and level glass.Automation system Arduino Mega 2560 microcontroller running well as the dispenser system mechanism. Resulting in a dispenser that can provide comfort for people, particularly in meeting the needs of drinking.Keywords : microcontrollers, Arduino Mega, Soil moisture sensor, Driver delay